2014
DOI: 10.7322/jhgd.81037
|View full text |Cite
|
Sign up to set email alerts
|

Visual motor integration and overall development of preterm and at term children at the beginning of schooling

Abstract: Objective: To investigate the influence of prematurity and low birth weight on development indicators, such as visual motor coordination, visual perceptive and fine motor skills of children in early schooling, as well as their relations with rates of global developmental delay. Method: It is a comparative study of case-control type. The research included 18 children with a history of preterm birth (Study Group), matched with 18 children without the same history (Comparison Group). These children were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…Thus, we suggested that greater access to information is related to greater availability of toys and, consequently, to a better stimulation of fine motor skills. Previous studies indicate that preterm children present significantly worse performance in writing, in sensory-motor tasks, manipulative tasks, visuomotor integration, visuoperceptive tasks and sensorial awareness when compared to children born at term 24 .…”
Section: Discussionmentioning
confidence: 93%
“…Thus, we suggested that greater access to information is related to greater availability of toys and, consequently, to a better stimulation of fine motor skills. Previous studies indicate that preterm children present significantly worse performance in writing, in sensory-motor tasks, manipulative tasks, visuomotor integration, visuoperceptive tasks and sensorial awareness when compared to children born at term 24 .…”
Section: Discussionmentioning
confidence: 93%
“…Some questions were answered; however, most are yet to be elucidated. [12,23] Several epidemiological studies have implicated the exposure to general anesthetic in early stages of life as responsible for a higher incidence of learning disorders. This effect was more evident after multiple exposures.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2014 study on premature infants with low birth weights, it was found that at a corrected age of 18-24 months, children displayed developmental delays in multiple areas such as motor skills, cognition and language 5 . Furthermore, infants who are born prematurely or extremely prematurely, are at risk for later visual-motor integration and higher-order visual problems which impact on school-related tasks [6][7][8][9] . Traditionally, occupational therapy offered to premature infants addressed specific deficits such as abnormal muscle tone, decreased range of motion at specific joints or a developmental delay which could have multiple causes 10 .…”
Section: Introductionmentioning
confidence: 99%